PENGGUNAAN SAJAK MATEMATIKA (CINQUAINS) PADA MATERI BANGUN DATAR - Indah Suciati (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2019)
Shape is a part of Geometry which is a branch of Mathematics consisting of triangles, squares, and polygon. Its application is often used in everyday. However, even though the concept is often encountered and used, there are still many students who experience difficulties in their understanding. To overcome this, the solution is given in the method of Cinquain". In the method, students are given a clear and interesting format to organize important thoughts and information. The steps are: (1) Introducing the concept of Cinquain, (2) Providing examples of attributes or material concepts, (3) Choosing a term that is in focus, (4) Providing time to examine, (5) Asking students to make cinquan independently or in groups, (6) Showing cinquain that have been made